Non-oriented electrical steel sheet and method for producing the same

By using insulating coatings containing metal phosphate salts and organic resins on non-oriented electromagnetic steel plates and controlling nitrogen content and surface roughness, the problems of insulating coating adhesion and NOx emissions are solved, achieving high performance and environmental protection Electromagnetic steel plate manufacturing.

CN116940709BActive Publication Date: 2025-02-18NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202280018048.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-30
Publication Date
2025-02-18
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

During the punching and stress-removing process of non-oriented electromagnetic steel plate, the adhesion of the insulating coating is difficult to maintain, and the NOx pollution caused during annealing is serious.

Method used

The insulating coating containing metal phosphate salt and organic resin was used, and the surface treatment agent was applied to the surface of the base material steel plate. The insulating coating was formed by heat treatment, and the nitrogen content of the insulating coating was controlled to be between 0.05 and 5.00 mass%, and the surface roughness was adjusted. The degree is within the range of 0.20 to 0.50 μm.

Benefits of technology

The excellent adhesion of the insulating coating and the suppression of NOx discharge amount are achieved, ensuring high performance and environmental protection of the electromagnetic steel plate during processing and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116940709B_ABST
    Figure CN116940709B_ABST
Patent Text Reader

Abstract

The non-oriented electrical steel sheet comprises a base steel sheet (10) and an insulating film (20) formed on the surface of the base steel sheet (10), wherein the insulating film (20) contains a phosphate metal salt and an organic resin, and the center line average roughness Ra of the insulating film (20) in the rolling direction of the base steel sheet (10) is 75 The center line average roughness Ra of the insulating coating (20) at right angles to the rolling direction 75 The arithmetic mean is 0.20 to 0.50 μm, and the nitrogen content in the insulating film (20) is 0.05 to 5.00 mass %.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-oriented electrical steel sheet and a method for producing the same.

[0002] This application claims priority based on Japanese Patent Application No. 2021-060499 filed in Japan on March 31, 2021, the contents of which are incorporated herein by reference. Background Art

[0003] Non-oriented electromagnetic steel sheets are used in driving motors for small household appliances such as audio equipment, and iron cores (motor cores (rotor cores, stator cores)) for driving motors for hybrid vehicles and electric vehicles.

[0004] An insulating film is formed on the surface of the non-oriented electromagnetic steel sheet. The insulating film is used, for example, to ensure the insulation between the electromagnetic steel sheets stacked as the stator core. That is, the insulating film is required to have excellent insulation. The insulating film is also required to have tight adhesion to the steel sheet. Therefore, the insulating film is required to have both insulation and tight adhesion.

[0005] Insulation coatings of non-oriented electrical steel sheets having excellent insulation and adhesion are proposed in, for example, International Publication No. 2016 / 136515 (Patent Document 1) and Japanese Patent Application Laid-Open No. 2017-141480 (Patent Document 2).

[0006] The electromagnetic steel sheet disclosed in Patent Document 1 has an insulating film on the surface of the steel sheet, which includes a binder composed of 100 parts by mass of a phosphate metal salt, 1 to 50 parts by mass of an organic resin having an average particle size of 0.05 to 0.50 μm, and a carboxylic acid compound having 2 to 50 carbon atoms in an amount of 0.1 to 10.0 parts by mass relative to 100 parts by mass of the solid matter of the binder, wherein the organic resin is one or more selected from acrylic resin, epoxy resin, and polyester resin. Patent Document 1 states that: Even when no chromium compound is contained, the insulating film has excellent adhesion, corrosion resistance, appearance, and rust resistance of the end surface after punching in addition to insulation.

[0007] The electromagnetic steel sheet disclosed in Patent Document 2 has an insulating film on the surface, the insulating film is composed of 100 parts by mass of a phosphate metal salt as a main component, 1 to 50 parts by mass of an acrylic resin having an average particle size of 0.05 to 0.50 μm and using a reactive emulsifier, and 0.5 to 10 parts by mass of a polyol, wherein the metal element of the phosphate metal salt is mixed with at least a divalent metal element and a trivalent metal element, and the mixing ratio of the divalent metal element is 30 to 80% by mass relative to the total mass of the metal element of the phosphate metal salt. Patent Document 2 states that: even if the insulating film is applied thinly to increase the space factor, the uniformity is good, there is no problem in insulation, and the adhesion to the resin during electrophoretic coating or molding is excellent.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2016 / 136515

[0011] Patent Document 2: Japanese Patent Application Publication No. 2017-141480 Summary of the invention

[0012] Technical problem to be solved by the invention

[0013] In addition, the manufacturing method of the stator core using non-oriented electromagnetic steel sheets is as follows. The non-oriented electromagnetic steel sheets are punched into a specified shape. The punched steel sheets (core blanks) are stacked and fixed to manufacture a laminated core. Coils are arranged in the slots of the stator core. During the punching process, the punched non-oriented electromagnetic steel sheets are given processing strain, and the magnetic properties are deteriorated. Therefore, in order to remove the processing strain, stress relief annealing is sometimes performed. Annealing is performed at a high temperature of more than 700°C. The insulating coating that is heated during annealing sometimes generates decomposition products caused by heating.

[0014] As mentioned above, the insulating coating of the non-oriented electrical steel sheet is required to have excellent adhesion, and excellent adhesion is required even after stress relief annealing. If the adhesion is low, the coating piece peeled off from the steel sheet enters between the stator core and the rotor core, hindering the rotation of the stator core and the rotor core. Depending on the situation, the rotor core may be damaged.

[0015] The decomposition products of the insulating coating generated by heating during annealing sometimes contain nitrogen oxides (so-called NOx) such as nitrogen monoxide (NO) and nitrogen dioxide (NO2). NOx can damage the annealing furnace or become a cause of air pollution. Therefore, it is preferable to suppress the emission of NOx during punching and annealing of the laminated core after lamination.

[0016] An object of the present invention is to provide a non-oriented electrical steel sheet having an insulating coating capable of achieving both excellent adhesion and suppression of NOx emission, and a method for producing the non-oriented electrical steel sheet having an insulating coating capable of achieving both excellent adhesion and suppression of NOx emission.

[0017] Technical means for solving technical problems

[0018] The non-oriented electrical steel sheet of the present invention comprises:

[0019] Base steel plate, and

[0020] an insulating film formed on the surface of the base steel plate;

[0021] The insulating film contains

[0022] Metal phosphates, and

[0023] Organic resins;

[0024] The center line average roughness Ra of the insulating coating in the rolling direction of the base steel plate 75 and the centerline average roughness Ra in the direction perpendicular to the rolling direction 75 The arithmetic mean is 0.20~0.50μm,

[0025] The nitrogen content in the insulating film is 0.05 to 5.00 mass %.

[0026] The method for producing a non-oriented electrical steel sheet of the present invention comprises:

[0027] A step of applying a surface treatment agent containing a phosphate metal salt and an organic resin to the surface of a base steel plate; and

[0028] The step of heating the base steel sheet coated with the surface treatment agent at a heat treatment temperature of 200 to 450° C., a dew point of 0 to 30° C., a heat treatment time of 10 to 60 seconds, and any one of the heating rates shown in the heating conditions (1) to (3) to form an insulating coating,

[0029] Heating conditions (1): When the concentration of the surface treatment agent is less than 16 wt%, the heating rate is 20-40 °C / s.

[0030] Heating condition (2): when the concentration of the surface treatment agent is 16 to less than 30 wt%, the heating rate is 5 to less than 20°C / s,

[0031] Heating condition (3): When the concentration of the surface treatment agent is 30 wt % or more, the heating rate is less than 5° C. / s.

[0032] Effects of the Invention

[0033] The non-oriented electrical steel sheet in the above aspect of the present invention has an insulating coating that can achieve both excellent adhesion and suppression of NOx emissions. The method for manufacturing a non-oriented electrical steel sheet in the above aspect of the present invention can manufacture a non-oriented electrical steel sheet having an insulating coating that can achieve both excellent adhesion and suppression of NOx emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a cross-sectional view of the non-oriented electrical steel sheet in the sheet thickness direction according to the present embodiment.

[0035] Figure 2 To enlarge Figure 1sectional view of the insulating coating 20 in FIG. DETAILED DESCRIPTION

[0036] The inventors of the present invention have conducted investigations and studies on achieving both excellent adhesion and suppression of NOx emission in an insulating film of a non-oriented electrical steel sheet.

[0037] The inventors of the present invention first studied a method for improving the adhesion of an insulating film of a non-oriented electrical steel sheet. The above-mentioned Patent Documents 1 and 2 describe that an insulating film containing a metal phosphate and an organic resin has excellent adhesion. Therefore, the inventors of the present invention studied a method for further improving the adhesion of an insulating film containing a metal phosphate and an organic resin.

[0038] The inventors of the present invention have found that, in the case of an insulating film containing the above-mentioned metal phosphate and an organic resin, adhesion is improved when the insulating film contains nitrogen. The reason why adhesion is improved when the insulating film contains nitrogen is not certain, but it is considered as follows, for example.

[0039] The base steel plate is a metal and has hydroxyl groups on its surface. In addition, the polarity of the metal phosphate is large. On the other hand, the organic resin has a small polarity because it contains a large amount of hydrocarbons with non-polar groups. Therefore, if the metal phosphate contains only the organic resin, the compatibility between the organic resin and the metal phosphate is low. In this case, the adhesion of the insulating film is low. However, if the insulating film contains nitrogen, the nitrogen increases the compatibility between the metal phosphate and the organic resin. Therefore, it is believed that the organic resin, the base steel plate and the metal phosphate are combined through hydrogen bonds, and the adhesion of the insulating film is improved.

[0040] However, simply by including nitrogen in the insulating film, the emission of NOx cannot be suppressed. Therefore, the nitrogen content in the insulating film is controlled on the premise that nitrogen is included. If the nitrogen content in the insulating film is reduced, the nitrogen that is the source of NOx generation is reduced, thereby suppressing the emission of NOx.

[0041] In addition, in order to improve the adhesion after stress relief annealing, the surface roughness of the insulating film is also an important factor. If the surface roughness is too small, large cracks are likely to occur during stress relief annealing, and the adhesion is reduced.

[0042] Based on the above research results, the inventors of the present invention have studied an insulating film that can achieve both excellent adhesion and suppression of NOx emissions. It was found that if the insulating film contains a phosphate metal salt and an organic resin, the nitrogen content in the insulating film is 0.05 to 5.00% by mass, and the center line average roughness Ra of the insulating film in the rolling direction of the base steel plate is 75 The center line average roughness Ra of the insulation coating in the direction perpendicular to the rolling direction 75When the arithmetic mean of the thickness is 0.20 to 0.50 μm, the adhesion of the insulating film is improved and the NOx emission can be suppressed.

[0043] The non-oriented electrical steel sheet of the present embodiment is completed based on the above-mentioned technical idea, and its gist is as follows. [1]

[0045] A non-oriented electromagnetic steel sheet having:

[0046] Base steel plate,

[0047] an insulating film formed on the surface of the base steel plate;

[0048] The insulating film contains

[0049] Metal phosphates, and

[0050] Organic resins;

[0051] The center line average roughness Ra of the insulating coating in the rolling direction of the base steel plate 75 The center line average roughness Ra of the insulating film in a direction perpendicular to the rolling direction 75 The arithmetic mean is 0.20~0.50μm,

[0052] The nitrogen content in the insulating film is 0.05 to 5.00 mass %. [2]

[0054] The non-oriented electrical steel sheet as described in [1],

[0055] The metal phosphate contains one or more selected from the group consisting of zinc phosphate, manganese phosphate, aluminum phosphate, and molybdenum phosphate.

[0056] The organic resin has epoxy resin as a main component.

[0057] Here, “containing epoxy resin as a main component” means that the content of epoxy resin in the organic resin is 50% or more in terms of mass %. [3]

[0059] The non-oriented electrical steel sheet as described in [1] or [2],

[0060] The insulating coating contains an amino compound. [4]

[0062] The non-oriented electrical steel sheet according to any one of [1] to [3],

[0063] The amino compound is one or more selected from the group consisting of alkylamines, alkanolamines, polyamine compounds, isocyanate compounds, blocked isocyanate compounds, aromatic amine compounds, and nitrogen-containing heterocyclic compounds. [5]

[0065] The non-oriented electrical steel sheet according to any one of [1] to [4],

[0066] The base steel plate contains, by mass%,

[0067] Si: 2.5-4.5%,

[0068] Al: 0.1-1.5%,

[0069] Mn: 0.2~4.0%.

[0070] In addition, the above-mentioned non-oriented electrical steel sheet can be produced by the following production method, for example. [6]

[0072] A method for manufacturing a non-oriented electromagnetic steel sheet, comprising:

[0073] A step of applying a surface treatment agent containing a metal phosphate and an organic resin to the surface of a base steel plate; and

[0074] The step of heating the base steel sheet coated with the surface treatment agent at a heat treatment temperature of 200 to 450° C., a dew point of 0 to 30° C., a heat treatment time of 10 to 60 seconds, and any one of the heating rates shown in the heating conditions (1) to (3) to form an insulating coating,

[0075] Heating conditions (1): When the concentration of the surface treatment agent is less than 16 wt%, the heating rate is 20-40 °C / s.

[0076] Heating condition (2): when the concentration of the surface treatment agent is 16 to less than 30 wt%, the heating rate is 5 to less than 20°C / s,

[0077] Heating condition (3): When the concentration of the surface treatment agent is 30 wt % or more, the heating rate is less than 5° C. / s.

[0078] Next, the non-oriented electrical steel sheet according to the present embodiment will be described in detail.

[0079] [Constitution of non-oriented electrical steel sheet]

[0080] Figure 1 2 is a cross-sectional view of a non-oriented electrical steel sheet according to the present embodiment in the sheet thickness direction. Figure 1The non-oriented electrical steel sheet 1 includes a base steel sheet 10 and an insulating film 20. The insulating film 20 is formed on the surface of the base steel sheet 10. Figure 1 In the embodiment, the insulating film 20 is formed on the upper surface and the lower surface of the base steel plate 10. However, the insulating film 20 may be formed on only one surface of the base steel plate 10. Next, the base steel plate 10 and the insulating film 20 will be described.

[0081] [Base steel plate 10]

[0082] The base steel sheet 10 can be appropriately selected from known steel sheets used as the non-oriented electrical steel sheet 1. That is, the base steel sheet 10 is not particularly limited as long as it is a known steel sheet used for the non-oriented electrical steel sheet 1.

[0083] The chemical composition of the base steel plate 10 contains basic elements, contains optional elements as needed, and the remainder is composed of Fe and impurities. The chemical composition of the base steel plate 10 contains the following elements, for example. Hereinafter, "%" means mass % unless otherwise specified.

[0084] [Basic elements]

[0085] The chemical composition of the base steel plate 10 contains Si, Al, and Mn as basic elements. These elements will be described below.

[0086] Si: 2.5-4.5%

[0087] Silicon (Si) increases the electrical resistance of steel and reduces eddy current loss. As a result, the iron loss of the steel plate is reduced. Si also increases the strength of steel. If the Si content is less than 2.5%, the above effect cannot be fully obtained. On the other hand, if the Si content is higher than 4.5%, the workability of the steel is reduced. Therefore, the Si content is 2.5 to 4.5%. The preferred lower limit of the Si content is 2.6%, and more preferably 2.7%. The preferred upper limit of the Si content is 4.3%, and more preferably 4.2%.

[0088] Al: 0.1~1.5%

[0089] Aluminum (Al) increases the electrical resistance of steel and reduces eddy current loss. As a result, the iron loss of the steel plate is reduced. If the Al content is less than 0.1%, the above effect cannot be fully obtained. On the other hand, if the Al content is higher than 1.5%, the saturation magnetic flux density decreases. Therefore, the Al content is 0.1 to 1.5%. The preferred lower limit of the Al content is 0.15%, and more preferably 0.2%. The preferred upper limit of the Al content is 1.4%, and more preferably 1.3%.

[0090] Mn: 0.2~4.0%

[0091] Manganese (Mn) increases the electrical resistance of steel and reduces eddy current loss. As a result, the iron loss of the steel plate is reduced. Mn also suppresses the formation of {111}<112> texture, which is not preferred for magnetic properties. If the Mn content is less than 0.2%, the above effect cannot be fully obtained. On the other hand, if the Mn content exceeds 4.0%, the texture changes and the hysteresis loss deteriorates. Therefore, the Mn content is 0.2-4.0%. The preferred lower limit of the Mn content is 0.3%, and more preferably 0.4%. The preferred upper limit of the Mn content is 3.8%, and more preferably 3.6%.

[0092] In the present embodiment, the chemical composition of the base steel plate 10 contains impurities. Here, the so-called impurities are elements mixed from ore or waste as raw materials, or from the manufacturing environment, etc. when the base steel plate 10 is industrially produced. Impurities are elements such as C, P, S, and N.

[0093] The chemical composition of the base steel plate 10 can be measured by a known chemical analysis method. For example, the chemical composition of the base steel plate 10 may be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry).

[0094] [Insulation coating 20]

[0095] As described above, the insulating film 20 is formed on the surface of the base steel sheet 10. After the non-oriented electromagnetic steel sheet 1 is processed into a core blank, it is stacked to form a motor core. The insulating film 20 reduces the eddy current between the stacked steel sheets (between the core blanks). As a result, the eddy current loss of the motor core can be reduced.

[0096] Figure 2 Is magnification Figure 1 20 is a cross-sectional view of the insulating film 20 in FIG. Figure 2 The insulating film 20 contains a phosphate metal salt 201 and an organic resin 202. In addition, the insulating film 20 does not contain chromium oxide. Next, the phosphate metal salt 201, the organic resin 202, and the amino compound are described.

[0097] [Phosphate metal salt 201]

[0098] The metal phosphate 201 functions as a binder of the insulating film 20. The metal phosphate 201 is a solid obtained by drying an aqueous solution (insulating film solution) containing phosphoric acid and metal ions. The type of phosphoric acid is not particularly limited, and known phosphoric acids can be used. Preferred phosphoric acids are one or more selected from the group consisting of orthophosphoric acid, metaphosphoric acid, and polyphosphoric acid.

[0099] The metal ions act on the corrosion resistance and adhesion of the insulating film 20. The type of the metal ions is not particularly limited. For example, the metal ions are one or more selected from the group consisting of Li, Al, Zn, Mg, Ca, Sr, Ti, Co, Mn, and Ni.

[0100] Preferably, the metal phosphate contains one or more selected from the group consisting of zinc phosphate, manganese phosphate, aluminum phosphate, and molybdenum phosphate. Zinc phosphate effectively improves the corrosion resistance of the insulating film 20. Manganese phosphate improves the heat resistance of the insulating film 20. Aluminum phosphate improves the adhesion of the insulating film 20 to the base steel plate 10 and improves the heat resistance of the insulating film 20. Molybdenum phosphate improves the heat resistance of the insulating film 20. The metal phosphate may contain the above-mentioned other metal elements other than Al and Zn.

[0101] [Organic resin 202]

[0102] Reference Figure 2 The organic resin 202 is dispersedly contained in the phosphate metal salt 201 which functions as a binder. The organic resin 202 suppresses the coarse growth of the phosphate metal salt 201 and promotes the polycrystallization of the phosphate metal salt 201. The organic resin 202 forms a dense insulating film 20.

[0103] The organic resin 202 is not particularly limited, and a known organic resin can be used. Preferably, the organic resin 202 is one or more selected from the group consisting of acrylic resin, styrene resin, polyvinyl acetate, epoxy resin, polyester resin, polyurethane resin, polyimide resin, phenol resin, melamine resin, silicone resin, polypropylene resin, and polyethylene resin.

[0104] Preferably, the organic resin 202 is an epoxy resin. Epoxy resin has excellent insulation and corrosion resistance. The type of epoxy resin is not particularly limited. For example, the epoxy resin is one or more selected from the group consisting of bisphenol A, F, B type, alicyclic type, glycidyl ether type, glycidyl ester type, biphenyl type, naphthalene type, phenol novolac type, o-cresol novolac type, tetraphenol ethane type, and trishydroxyphenylmethane type.

[0105] More specifically, the epoxy resin is, for example, one or more selected from the group consisting of bisphenol A diglycidyl ether, caprolactone ring-opening adduct of bisphenol A-diglycidyl ether, bisphenol F-diglycidyl ether, bisphenol S-diglycidyl ether, novolac glycidyl ether, dipolyacid glycidyl ether, glycidyl ether derivatives, polyglycidyl esters, dipolyacid glyceryl esters, and glycidyl ester derivatives.

[0106] [Method for measuring the metal phosphate 201 and the organic resin 202 in the insulating film 20]

[0107] The metal phosphate 201 and the organic resin 202 in the insulating film 20 can be measured by the following method. The gas generation behavior when the non-oriented electrical steel sheet 1 having the insulating film 20 formed thereon is heated is analyzed using the pyrolysis-gas chromatography / mass spectrometry (Py-GC / MS) method (hereinafter referred to as the GC / MS method) to determine the presence or absence of the organic resin 202 and the type of the organic resin 202. The organic resin can also be determined by using the above-mentioned GC / MS method and Fourier transform infrared spectroscopy (FT-IR) in combination.

[0108] Furthermore, when chemical analysis based on energy dispersive X-ray spectroscopy (EDS) or ICP-AES is performed on the insulating film 20 and P and metal elements (Zn, Al, etc.) are detected, it is determined that the insulating film 20 contains metal phosphate.

[0109] [Insulation coating surface roughness]

[0110] The surface roughness of the insulating film 20 is Ra measured in the rolling direction of the base steel plate 10. 75 (center line average roughness) and Ra in the direction perpendicular to the rolling direction of the base steel plate 10 75 The arithmetic mean calculated later is 0.20 to 0.50 μm. Surface roughness Ra 75 When the particle size is less than 0.02 μm, large cracks are likely to occur during stress relief annealing, and the adhesion is reduced. When the particle size is more than 0.50 μm, the amount of NOx generated may increase.

[0111] Surface roughness Ra 75 A more preferred lower limit is 0.25 μm, and a more preferred upper limit is 0.40 μm. 75 It is the center line average roughness described in JIS B0601:2013. Ra 75 The measurement can be performed in accordance with JIS B0601:2013.

[0112] [Nitrogen Content in Insulating Film 20]

[0113] In the insulating film 20 of the present embodiment containing the metal phosphate 201 and the organic resin 202, when the nitrogen content is less than 0.05 mass%, the adhesion of the insulating film 20 cannot be improved. On the other hand, in the insulating film 20 of the present embodiment containing the metal phosphate 201 and the organic resin 202, when the nitrogen content exceeds 5.00 mass%, the emission of NOx during annealing cannot be suppressed. Therefore, the nitrogen content in the insulating film 20 is 0.05 to 5.00 mass%. The lower limit of the nitrogen content in the insulating film 20 is 0.10 mass%, and more preferably 0.15 mass%. The upper limit of the nitrogen content in the insulating film 20 is preferably 4.80 mass%, more preferably 4.50 mass%, more preferably 4.00 mass%, and further preferably 3.00 mass%.

[0114] [Method for measuring nitrogen content in insulating film 20]

[0115] The nitrogen content in the insulating film 20 is measured by the following method. For the non-oriented electrical steel sheet 1 on which the insulating film 20 is formed, the content of each element in the insulating film 20 is measured using an energy dispersive X-ray spectrometer (EDS) device. The surface of the non-oriented electrical steel sheet 1 (insulating film 20) is analyzed at five random locations. From the analysis results, the peak intensity of iron (Fe) is removed, and the total of the peaks of the remaining elements is taken as 100 mass %, and the nitrogen content (mass %) is calculated.

[0116] [Amino compounds]

[0117] Preferably, the insulating film 20 contains an amino compound. In the present specification, the amino compound is not necessarily limited to a compound containing an amino group. The amino compound is a compound containing at least one selected from the group consisting of a primary amine (R1-NH2), a secondary amine (R1-NH-R2), a tertiary amine (R1-NR2-R3), an isocyanate group (R1-N=C=O), an amide group (R1-CO-N-R2R3), an imino group (R2-CO-NR1-CO-R3), a nitrile group (R-CN), a hydrazide (R1-CO-NR2NR3R4), a guanidine group (R-NH-CNH-NH2) and a nitrogen-containing heterocyclic ring. The amino compound may be contained in the insulating film 20 as a part of the organic resin 202, or may be contained in the insulating film 20 independently of the organic resin 202. In any case, the amino compound increases the polarity of the organic resin 202. Thus, the adhesion of the insulating film 20 is improved. Preferably, the amino compound is not included in the insulating film 20 as a part of the organic resin 202. That is, the organic resin 202 is preferably an organic resin 202 containing an amino compound.

[0118] Preferably, the amino compound is one or more selected from the group consisting of alkylamines, alkanolamines, polyamine compounds, isocyanate compounds, blocked isocyanate compounds, aromatic amine compounds, and nitrogen-containing heterocyclic compounds.

[0119] [Method for Determining Amino Compound in Insulating Film 20]

[0120] The amino compound in the insulating film 20 can be identified as follows: The gas generation behavior when the non-oriented electrical steel sheet 1 having the insulating film 20 formed thereon is analyzed by the above-mentioned GC / MS method and Fourier transform infrared spectroscopy (FT-IR) to identify the presence or absence of the amino compound and the type of the amino compound.

[0121] [Preferred Film Thickness of Insulation Film 20]

[0122] The film thickness of the insulating film 20 is not particularly limited. The preferred film thickness of the insulating film 20 is 0.2 to 1.60 μm. When the film thickness is 0.2 to 1.60 μm, the insulating film 20 exhibits more excellent insulation. However, even when the film thickness of the insulating film 20 is other than 0.2 to 1.60 μm, both excellent adhesion and suppression of NOx emissions can be achieved.

[0123] As described above, the non-oriented electrical steel sheet 1 of the present embodiment includes a base steel sheet 10 and an insulating film 20 formed on the surface of the base steel sheet 10. The insulating film 20 contains a metal phosphate 201, an organic resin 202, and an amino compound. The nitrogen content in the insulating film 20 is 5.0 mass % or less. Therefore, both excellent adhesion and suppression of NOx emission can be achieved.

[0124] [Manufacturing method]

[0125] An example of a method for manufacturing the non-oriented electromagnetic steel sheet 1 of the present embodiment is described. The manufacturing method described below is an example for manufacturing the non-oriented electromagnetic steel sheet 1. Therefore, the non-oriented electromagnetic steel sheet 1 may be manufactured by a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing the non-oriented electromagnetic steel sheet 1.

[0126] An example of a method for manufacturing the non-oriented electrical steel sheet 1 of the present embodiment includes: a step of applying a surface treatment agent containing a phosphate metal salt 201 and an organic resin 202 to the surface of a base steel sheet 10 (coating step); and a step of heating the base steel sheet 10 coated with the surface treatment agent to form an insulating film 20 (sintering step). Each step will be described below.

[0127] [Coating process]

[0128] In the coating step, the surface treatment agent is applied to the surface of the base steel plate 10. The coating method is not particularly limited. A known coating method can be applied. Examples of the coating method include a roll coating method, a spray coating method, and a dipping method.

[0129] [About surface treatment agents]

[0130] The surface treatment agent contains a metal phosphate and an organic resin. Here, the metal phosphate and the organic resin in the surface treatment agent use the above-mentioned metal phosphate and organic resin. When preparing the metal phosphate solution, it is preferred to mix various phosphoric acids such as orthophosphoric acid with at least one of oxides, carbonates, and hydroxides of metal ions.

[0131] [About the content of organic resin in the surface treatment agent]

[0132] The content of the organic resin in the surface treatment agent is set to 1.0 to 70.0 parts by mass relative to 100.0 parts by mass of the metal phosphate. When the content of the organic resin is less than 1.0 parts by mass, the coarsening of the metal phosphate cannot be sufficiently suppressed. In this case, the adhesion of the insulating film 20 to the parent steel plate 10 is reduced. On the other hand, when the content of the organic resin is higher than 70.0 parts by mass, the insulating film contains an excessive amount of organic resin. In this case, the adhesion of the insulating film 20 to the parent steel plate 10 is reduced. Therefore, the content of the organic resin in the surface treatment agent is set to 1.0 to 70.0 parts by mass relative to 100 parts by mass of the metal phosphate.

[0133] The preferred lower limit of the content of the organic resin is preferably 2.0 parts by mass, more preferably 3.0 parts by mass, relative to 100.0 parts by mass of the metal phosphate. The preferred upper limit of the content of the organic resin is 65.0 parts by mass, more preferably 60.0 parts by mass, more preferably 55.0 parts by mass, and further preferably 50.0 parts by mass, relative to 100.0 parts by mass of the metal phosphate.

[0134] [About amino compounds]

[0135] The surface treatment agent may contain an amino compound in addition to the metal phosphate and the organic resin. The amino compound used is the above-mentioned amino compound. The amino compound is contained in the surface treatment agent by any of the following methods.

[0136] (1) Amino compounds as organic resins

[0137] (2) Amino compounds as curing agents for organic resins

[0138] (3) Amino compounds as modifiers for organic resins

[0139] (4) Amino compounds as mixtures

[0140] (1) Amino compounds as organic resins

[0141] Amino compounds can also be contained in the surface treatment agent as part of the organic resin. At this time, specifically, an organic resin containing at least one selected from the group consisting of primary amine (R1-NH2), secondary amine (R1-NH-R2), tertiary amine (R1-NR2-R3), isocyanate group (R1-N=C=O), amide group (R1-CO-N-R2R3), imino group (R2-CO-NR1-CO-R3), nitrile group (R-CN), hydrazide (R1-CO-NR2NR3R4), guanidine group (R-NH-CNH-NH2), and nitrogen-containing heterocyclic ring is used. Preferably, an organic resin containing at least one selected from the group consisting of alkylamine, alkanolamine, polyamine compound, isocyanate compound, blocked isocyanate compound, aromatic amine compound, and nitrogen-containing heterocyclic compound, water-soluble imide resin, self-emulsifying polyimide resin, water-based amino resin (water-based melamine, water-based benzoguanamine, water-based urea-formaldehyde resin) is used.

[0142] (2) Amino compounds as curing agents for organic resins

[0143] Amino compounds can be contained in the surface treatment agent as a curing agent for organic resins. At this time, specifically, a curing agent containing at least one selected from the group consisting of primary amine (R1-NH2), secondary amine (R1-NH-R2), tertiary amine (R1-NR2-R3), isocyanate group (R1-N=C=O), amide group (R1-CO-N-R2R3), imino group (R2-CO-NR1-CO-R3), nitrile group (R-CN), hydrazide (R1-CO-NR2NR3R4), guanidine group (R-NH-CNH-NH2), and nitrogen-containing heterocyclic ring is used. Preferably, a curing agent containing at least one selected from the group consisting of alkylamine, alkanolamine, polyamine compound, isocyanate compound, blocked isocyanate compound, aromatic amine compound, and nitrogen-containing heterocyclic compound is used.

[0144] (3) Amino compounds as modifiers for organic resins

[0145] Amino compounds can also be contained in the surface treatment agent as a modifier for organic resins. At this time, specifically, a modifier containing at least one selected from the group consisting of primary amine (R1-NH2), secondary amine (R1-NH-R2), tertiary amine (R1-NR2-R3), isocyanate group (R1-N=C=O), amide group (R1-CO-N-R2R3), imino group (R2-CO-NR1-CO-R3), nitrile group (R-CN), hydrazide (R1-CO-NR2NR3R4), guanidine group (R-NH-CNH-NH2), and nitrogen-containing heterocyclic ring is used. Preferably, a modifier containing at least one selected from the group consisting of alkylamine, alkanolamine, polyamine compound, isocyanate compound, blocked isocyanate compound, aromatic amine compound, and nitrogen-containing heterocyclic compound is used.

[0146] (4) Amino compounds as mixtures

[0147] The amino compound can also be contained in the surface treatment agent as a mixture. In this case, specifically, a compound containing at least one selected from the group consisting of a primary amine (R1-NH2), a secondary amine (R1-NH-R2), a tertiary amine (R1-NR2-R3), an isocyanate group (R1-N=C=O), an amide group (R1-CO-N-R2R3), an imino group (R2-CO-NR1-CO-R3), a nitrile group (R-CN), a hydrazide (R1-CO-NR2NR3R4), a guanidine group (R-NH-CNH-NH2), and a nitrogen-containing heterocyclic ring is used. Preferably, a compound containing at least one selected from the group consisting of an alkylamine, an alkanolamine, a polyamine compound, an isocyanate compound, a blocked isocyanate compound, an aromatic amine compound, and a nitrogen-containing heterocyclic compound is used.

[0148] When the surface treatment agent contains an amino compound, the content of the amino compound in the surface treatment agent is 1 to 70 parts by mass relative to 100.0 parts by mass of the metal phosphate. If the content of the amino compound is 1 part by mass or more, the compatibility of the organic resin is more stably improved. Therefore, the adhesion of the insulating film is more stably improved. On the other hand, if the content of the amino compound is 70 parts by mass or less, the insulation of the insulating film after stress relief annealing is more stably improved. Therefore, when the amino compound is contained, the content of the amino compound in the surface treatment agent is set to 1 to 70 parts by mass relative to 100.0 parts by mass of the metal phosphate.

[0149] [About curing agent]

[0150] The surface treatment agent may contain a curing agent in addition to the metal phosphate and the organic resin. The curing agent cures the organic resin. As described above, when an amino compound is contained as a curing agent, the curing agent contains an amino compound. However, the curing agent is not limited to a curing agent containing an amino compound. For example, the curing agent may be one or more selected from the group consisting of a polyamine curing agent, an acid anhydride curing agent, and a hydroxymethyl-containing initial condensate.

[0151] The polyamine curing agent may be, for example, one or more selected from the group consisting of aliphatic polyamines, alicyclic polyamines, aromatic polyamines, polyamidoamines, and modified polyamines.

[0152] The acid anhydride curing agent is, for example, one or more selected from the group consisting of monofunctional acid anhydrides (phthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hexachloronadic anhydride, etc.), bifunctional acid anhydrides (pyromellitic anhydride, benzophenonetetracarboxylic anhydride, ethylene glycol bis(trimellitic anhydride), methylcyclohexenetetracarboxylic anhydride, etc.), and free acid anhydrides (trimellitic anhydride, polyazelaic anhydride, etc.).

[0153] The methylol group-containing initial condensate is, for example, one or more selected from the group consisting of novolac-type or resol-type phenol resins, urea resins, and melamine resins.

[0154] When the surface treatment agent contains a curing agent, the content of the curing agent in the surface treatment agent is 0 to 50.0 parts by mass relative to 100.0 parts by mass of the metal phosphate. When the surface treatment agent contains a curing agent, the curing agent promotes the curing of the organic resin. If the content of the curing agent is 50.0 parts by mass or less, the adhesion of the insulating coating 20 to the base steel plate 10 is more stably improved. Therefore, when the curing agent is contained, the content of the curing agent in the surface treatment agent is set to 0 to 50.0 parts by mass relative to 100.0 parts by mass of the metal phosphate.

[0155] The preferred lower limit of the content of the curing agent is 0.5 parts by mass, more preferably 1.0 parts by mass, and even more preferably 2.0 parts by mass, relative to 100.0 parts by mass of the metal phosphate. The upper limit of the content of the curing agent is 45.0 parts by mass, more preferably 40.0 parts by mass, and even more preferably 35.0 parts by mass, relative to 100.0 parts by mass of the metal phosphate.

[0156] [Sintering process]

[0157] In the sintering process, the base steel plate 10 coated with the surface treatment agent is heated to form the insulating film 20. The sintering conditions are a heat treatment temperature of 200 to 450°C, a dew point of 0 to 30°C, a heat treatment time of 10 to 60 seconds, and any heating rate shown in heating conditions (1) to (3). By satisfying these conditions, the center line average roughness Ra of the insulating film 20 in the rolling direction of the base steel plate 10 is 75 The center line average roughness Ra of the insulating film 20 in the direction perpendicular to the rolling direction of the base steel plate 10 is 75 The arithmetic mean can be set to 0.20 to 0.50 μm.

[0158] Heating conditions (1): When the concentration of the surface treatment agent is less than 16 wt%, the heating rate is 20-40 °C / s.

[0159] Heating conditions (2): When the concentration of the surface treatment agent is 16 to less than 30 wt%, the heating rate is 5 to less than 20 °C / s.

[0160] Heating condition (3): When the concentration of the surface treatment agent is 30 wt % or more, the heating rate is less than 5° C. / s.

[0161] For example, by including the above-mentioned amino compound in the surface treatment agent as an organic resin, a curing agent, a modifier, or a mixture, and appropriately adjusting the conditions within the above-mentioned range of sintering conditions, the nitrogen content in the insulating film can be controlled to be 0.05 to 5.00% by mass. When heating at a heating rate lower than the heating conditions (1) to (3), excessive heating occurs, and the nitrogen content in the insulating film becomes less than 0.05% by mass. On the other hand, when heating at a heating rate exceeding the heating conditions (1) to (3), boiling collapse occurs, and the formation of the insulating film 20 may not be appropriately controlled, and the nitrogen content in the insulating film may exceed 5.00% by mass.

[0162] Through the above-mentioned manufacturing steps, the non-oriented electrical steel sheet 1 is manufactured.

[0163] Example

[0164] The effects of the non-oriented electrical steel sheet of the present embodiment will be described in more detail with reference to the examples. The conditions in the following examples are one example of conditions adopted to confirm the feasibility and effects of the non-oriented electrical steel sheet of the present embodiment. Therefore, the non-oriented electrical steel sheet of the present embodiment is not limited to this one example of conditions.

[0165] A base steel plate (non-oriented electromagnetic steel plate) containing Si: 3.1%, Al: 0.6%, Mn: 0.2%, the remainder being Fe and impurities, and having a thickness of 0.25 mm was prepared. A coating process was performed on the prepared base steel plate. Specifically, a surface treatment agent having a composition shown in Table 1 was applied to the surface of the base steel plate by a coating device using a rubber roller.

[0166] [Table 1]

[0167]

[0168] The column "Phosphate metal salt (100 parts by mass)" in Table 1 shows the type of the phosphate metal salt contained in the surface treatment agent and the mass ratio of the phosphate metal salt. For example, in surface treatment agent No. 1, the phosphate metal salt is composed of aluminum phosphate. In surface treatment agent No. 3, aluminum phosphate and magnesium phosphate of the phosphate metal salt are contained in a mass ratio of 5:5. In surface treatment agent No. 4, aluminum phosphate and molybdenum phosphate of the phosphate metal salt are contained in a mass ratio of 6:4.

[0169] The "Types" A to C in the "Organic Resin" column in Table 1 are as follows

[0170] A: Bisphenol A epoxy resin with an epoxy equivalent of 5000 is modified with methacrylic acid and ethyl acrylate to make an acrylic modified epoxy resin, and then reacted and emulsified with dimethylethanolamine to form an epoxy resin emulsion containing amino compounds.

[0171] B: Epoxy resin amine adduct formed by dissolving bisphenol A epoxy resin with an epoxy equivalent of 980 in butoxyethanol and reacting it with N-methylethanolamine at 90°C

[0172] C: Epoxy resin emulsion obtained by forcibly stirring and emulsifying bisphenol A epoxy resin with an epoxy equivalent of 300 using an emulsifier

[0173] The "amount of compounding" in the "organic resin" column in Table 1 indicates the mass parts of the organic resin when the metal phosphate is taken as 100 mass parts.

[0174] "Types" a to d in the "Curing Agent" column in Table 1 are as follows.

[0175] a: Polyimide resin dissolved and dispersed in water

[0176] b: An epoxy resin-amine adduct curing agent prepared by reacting hexaoxadicyclopenta ...

[0177] c: Polyamidoamine dissolved and dispersed in water

[0178] d: Maleic anhydride dispersed in water

[0179] The "amount of compounding" in the "curing agent" column in Table 1 indicates the mass parts of the curing agent when the metal phosphate is 100 mass parts.

[0180] The surface treatment agent of each number was applied at a coating amount of 0.8 g / m 2 The surface of the base steel plate is coated with the surface treatment agent. The base steel plate coated with the surface treatment agent is subjected to a sintering treatment. The heat treatment temperature of each test number is 300°C, the dew point is 30°C, and the heat treatment time is 60 seconds. The heating rate of the sintering treatment of each test number is shown in Table 2. Through the above process, a non-oriented electromagnetic steel plate with an insulating coating formed on the surface of the base steel plate is manufactured.

[0181] [Table 2]

[0182]

[0183] [Evaluation Test 1]

[0184] The manufactured non-oriented electrical steel sheets were subjected to a surface roughness measurement test, a nitrogen content measurement test using EDS, an insulation evaluation test, a corrosion resistance evaluation test, a dissolution evaluation test, and a content identification test using a GC / MS method.

[0185] The surface roughness was measured using a commercially available surface roughness measuring device, SE3500 manufactured by Kosaka Laboratory, and the length of the measurement was 10 mm in the rolling direction of the base steel plate and in two directions perpendicular to the rolling direction of the base steel plate. The centerline average roughness (Ra 75 , μm), and the arithmetic average of the two directions was taken as the measured value. The measurement was based on JIS B0601:2013. In addition, Ra in Table 2 means Ra 75 .

[0186] [Test for determination of nitrogen content by EDS]

[0187] The nitrogen content in the insulating film of the non-oriented electrical steel sheet of each test number was measured by the following method. For the non-oriented electrical steel sheet formed with the insulating film, the content of each element in the insulating film was measured using an energy dispersive X-ray spectrometer. The surface of any five locations of the non-oriented electrical steel sheet (insulating film) was analyzed. From the analysis results, the peak intensity of iron (Fe) was removed, and the total of the peaks of the remaining elements was taken as 100% by mass to calculate the nitrogen content (mass %). The results are shown in the "[N] concentration (%) based on EDS" column of Table 2.

[0188] [Insulation evaluation test]

[0189] The insulation properties of the non-oriented electrical steel sheets of each test number were evaluated by the following method. The interlayer resistance of the non-oriented electrical steel sheets of each test number was measured according to JIS C2550-4: 2019. Based on the obtained interlayer resistance values, the insulation properties were evaluated as follows.

[0190] 4 (◎): interlayer resistance value is 30Ω·cm 2 / More than

[0191] 3(○): interlayer resistance value is 10Ω·cm 2 / piece or more and less than 30Ω·cm 2 / open

[0192] 2(△): interlayer resistance is 3Ω·cm 2 / piece or more and less than 10Ω·cm 2 / Sheet 1 (×): Interlayer resistance is less than 3Ω·cm 2 / open

[0193] The obtained insulation evaluation is shown in the "Insulation" column of Table 2. Evaluations 4 and 3 were regarded as passing.

[0194] [Corrosion resistance evaluation test]

[0195] The corrosion resistance of the non-oriented electromagnetic steel sheet of each test number was evaluated by the following method. A steel sheet sample with a width of 30 mm and a length of 300 mm was taken from the non-oriented electromagnetic steel sheet of each test number. Based on the salt spray test described in JIS Z2371:2015, a 5% NaCl aqueous solution was allowed to naturally settle on the steel sheet sample in an atmosphere of 35°C for 7 hours. Thereafter, the area ratio of the rusted area on the surface of the steel sheet sample (hereinafter referred to as the rust area ratio) was calculated. Based on the calculated rusted area, the corrosion resistance was evaluated by the following 10-point evaluation.

[0196] 10: Rust area rate is 0%

[0197] 9: Rust area ratio is less than 0.10%

[0198] 8: The rust area ratio is higher than 0.10% and less than 0.25%

[0199] 7: The rust area ratio is higher than 0.25% and less than 0.50%

[0200] 6: Rust area ratio is higher than 0.50% and less than 1.00%

[0201] 5: Rust area ratio is higher than 1.00% and less than 2.50%

[0202] 4: Rust area ratio is higher than 2.50% and less than 5.00%

[0203] 3: Rust area ratio is higher than 5.00% and less than 10.00%

[0204] 2: Rust area ratio is higher than 10.00% and less than 25.00%

[0205] 1: The rust area ratio is higher than 25.00% and less than 50.00%

[0206] The obtained corrosion resistance is shown in the column of "Characteristic corrosion resistance before stress relief annealing" in Table 2. A score of 5 or more was considered acceptable.

[0207] [Dissolution resistance evaluation test]

[0208] For the non-oriented electrical steel sheets of each test number, the dissolution resistance was evaluated by the following method. From the non-oriented electrical steel sheets of each test number, a steel sheet sample with a width of 30 mm and a length of 300 mm was taken. The steel sheet sample was boiled in boiling pure water for 10 minutes. The amount of phosphoric acid dissolved in the boiled pure water (solution) was measured. Specifically, the boiled pure water (solution) was cooled. The solution was diluted with pure water, and the phosphoric acid concentration in the solution was measured by ICP-AES. The amount of phosphoric acid dissolved (mg / m 2 The results are shown in the "Dissolution" column of Table 2. If the amount of phosphoric acid dissolved is less than 140 mg / m 2 , it is considered qualified (excellent dissolution resistance).

[0209] [GC / MS-based content determination test]

[0210] The organic resin in the insulating film of each test number was determined by the following method. The gas generation behavior when the non-oriented electrical steel sheet with the insulating film formed thereon was heated was analyzed by GC / MS method to determine the presence or absence of the organic resin and the type of the organic resin. As a result, it was confirmed that the insulating film of any test number contained epoxy resin and amino compounds.

[0211] [Evaluation Test 2]

[0212] The non-oriented electrical steel sheets of the respective test numbers were subjected to an adhesion evaluation test, a corrosion resistance evaluation test, and a NOx generation amount measurement test.

[0213] [Adhesion evaluation test]

[0214] For the non-oriented electromagnetic steel sheets of each test number, the adhesion is evaluated by the following method. From the non-oriented electromagnetic steel sheets of each test number, a steel sheet sample with a width of 30 mm and a length of 300 mm is taken. The steel sheet sample is subjected to stress relief annealing. During the stress relief annealing, the annealing temperature is set to 800°C and the annealing time is set to 2 hours in a nitrogen gas flow. An adhesive tape is attached to the insulating coating of the steel sheet sample after the stress relief annealing. The steel sheet sample with the adhesive tape attached is wound around a metal rod with a diameter of 10 mm. Thereafter, the steel sheet sample is separated from the metal rod. That is, a bend with a diameter of 10 mm is given to the steel sheet sample. Thereafter, the adhesive tape is peeled off from the steel sheet sample, and the proportion (area ratio) of the insulating coating that has not been peeled off from the base steel sheet is measured. Based on the obtained area ratio, the adhesion is evaluated as follows.

[0215] 4 (◎): The area ratio of the remaining insulating film is 100%. That is, the insulating film is not peeled off.

[0216] 3 (○): The area ratio of the remaining insulating film is 90% or more and less than 100%

[0217] 2 (△): The area ratio of the remaining insulating film is 50% or more and less than 90%

[0218] 1(×): The area ratio of the remaining insulation coating is less than 50%

[0219] The obtained adhesion evaluation is shown in the "Adhesion" column of Table 2. Evaluation 4, evaluation 3, and evaluation 2 were considered acceptable.

[0220] [Corrosion resistance evaluation test]

[0221] Stress relief annealing was performed on the non-oriented electrical steel sheets of each test number. Annealing was performed at 750°C for 2 hours in a nitrogen gas flow. The corrosion resistance of the non-oriented electrical steel sheets of each test number was evaluated by the following method. A steel sheet sample with a width of 30 mm and a length of 120 mm was taken from the non-oriented electrical steel sheets of each test number. According to the high temperature and high humidity test described in JIS C60068-3-4:2001, the temperature was 25 to 40°C and the dew point was maintained for 240 hours at a cycle of 90 to 95% and 95 to 100%. Thereafter, the area ratio of the rusted region (hereinafter referred to as the rust area ratio) was calculated on the surface of the steel sheet sample. The corrosion resistance was evaluated by the following 10-point evaluation based on the calculated rusted area.

[0222] 10: Rust area rate is 0%

[0223] 9: Rust area ratio is less than 0.10%

[0224] 8: The rust area ratio is higher than 0.10% and less than 0.25%

[0225] 7: The rust area ratio is higher than 0.25% and less than 0.50%

[0226] 6: Rust area ratio is higher than 0.50% and less than 1.00%

[0227] 5: Rust area ratio is higher than 1.00% and less than 2.50%

[0228] 4: Rust area ratio is higher than 2.50% and less than 5.00%

[0229] 3: Rust area ratio is higher than 5.00% and less than 10.00%

[0230] 2: Rust area ratio is higher than 10.00% and less than 25.00%

[0231] 1: The rust area ratio is higher than 25.00% and less than 50.00%

[0232] The obtained corrosion resistance is shown in the column of "Characteristic corrosion resistance after stress relief annealing" in Table 2. A score of 5 or more was regarded as passing.

[0233] [NOx generation measurement test]

[0234] For the non-oriented electrical steel sheets of each test number, the NOx generation amount was measured by the following method. A test piece with a size of 150 mm in width and 200 mm in length was obtained from the non-oriented electrical steel sheets of each test number. The test piece was annealed in a vacuum annealing furnace at 750°C × 2 hours in a nitrogen atmosphere, and the generated gas was absorbed by the absorbing liquid through gas flow. Thereafter, the NOx amount was measured by the ion chromatography method of JISK 0104. The results are shown in the "NOx Generation (ppm)" column of Table 2. Less than 1000 ppm is considered qualified.

[0235] [Evaluation results]

[0236] The evaluation results are shown in Table 2. Referring to Table 2, the insulating coating of the non-oriented electrical steel sheets of Test Nos. 1 to 7 and Test Nos. 9 to 10 contains a metal phosphate and an organic resin. In addition, the heating rate in the sintering process satisfies the heating conditions (1) to (3). Therefore, the nitrogen content in the insulating coating is 0.05 to 5.00 mass%. As a result, both excellent adhesion and suppression of NOx emissions can be achieved.

[0237] On the other hand, in Test No. 8, the temperature increase rate in the sintering step was too slow. Therefore, the nitrogen content in the insulating film was less than 0.05 mass %. As a result, although the amount of NOx generated was low, the adhesion was low.

[0238] In test numbers 11 to 13, the heating rate in the sintering process was too fast. Therefore, the nitrogen content in the insulating film exceeded 5.00 mass%. As a result, although the adhesion was excellent, the amount of NOx generated was too much. No. 14 had a too fast heating rate. Therefore, the surface roughness was higher than 0.50 μm. As a result, the amount of NOx generated in No. 14 was too much. No. 15 had a too slow heating rate. Therefore, the surface roughness was less than 0.20. As a result, No. 15 had low adhesion.

[0239] The embodiments of the present disclosure are described above. However, the above embodiments are only examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above embodiments, and the above embodiments can be appropriately changed and implemented within the scope of the purpose.

[0240] Description of Reference Numerals

[0241] 1 Non-oriented electromagnetic steel sheet

[0242] 10 Base steel plate

[0243] 20 Insulation coating

[0244] 201 Metal phosphate

[0245] 202 Organic resin

Claims

1. A non-oriented electromagnetic steel sheet comprising: Base steel plate; and The insulating film formed on the surface of the base steel plate, The insulating coating comprises: Metal phosphates; and Organic resin, The center line average roughness Ra of the insulating coating in the rolling direction of the base steel plate 75 The center line average roughness Ra of the insulating film in a direction perpendicular to the rolling direction 75 The arithmetic mean is 0.20~0.50μm, The nitrogen content in the insulating film is 0.05 to 5.00 mass %.

2. The non-oriented electrical steel sheet according to claim 1, The metal phosphate contains one or more selected from the group consisting of zinc phosphate, manganese phosphate, aluminum phosphate, and molybdenum phosphate. The organic resin has epoxy resin as a main component.

3. The non-oriented electrical steel sheet according to claim 1 or 2, The insulating film contains an amino compound. The amino compound is one or more selected from the group consisting of alkylamines, alkanolamines, polyamine compounds, isocyanate compounds, blocked isocyanate compounds, aromatic amine compounds, and nitrogen-containing heterocyclic compounds.

4. The non-oriented electrical steel sheet according to any one of claims 1 to 3, The base steel plate contains, by mass%, Si: 2.5-4.5%, Al:0.1~1.5%、 Mn: 0.2~4.0%.

5. A method for producing a non-oriented electrical steel sheet according to claim 1, comprising: A step of applying a surface treatment agent containing a phosphate metal salt and an organic resin to the surface of a base steel plate; and The step of heating the base steel sheet coated with the surface treatment agent at a heat treatment temperature of 200 to 450° C., a dew point of 0 to 30° C., a heat treatment time of 10 to 60 seconds, and any one of the heating rates shown in the heating conditions (1) to (3) to form an insulating coating, Heating conditions (1): When the concentration of the surface treatment agent is less than 16 wt%, the heating rate is 20-40 °C / s. Heating condition (2): when the concentration of the surface treatment agent is 16 to less than 30 wt%, the heating rate is 5 to less than 20°C / s, Heating condition (3): When the concentration of the surface treatment agent is 30 wt % or more, the heating rate is less than 5° C. / s.

Citation Information

Patent Citations

  • Electromagnetic steel sheet and method for manufacturing the same

    JP2017141480A

  • Electro-optical device and electronic apparatus

    JP2021060499A

  • Electromagnetic steel sheet and method for producing electromagnetic steel sheet

    WO2016136515A1

  • Method for forming insulating film containing no chromium compound, capable of stress relieving annealing and excellent in corrosion resistance on surface of silicon steel sheet

    JP1998046350A

  • Silicon steel sheet covered with insulation film and production method therefor

    JP2002249881A